DNA Barcoding, GIS-Facilitated Seed Germination and Pilot Cultivation of Teucrium luteum subsp. gabesianum (Lamiaceae), a Tunisian Local Endemic with Potential Medicinal and Ornamental Value - Stefanos Kostas; Stefanos Hatzilazarou; Elias Pipinis; Soumaya Bourgou; Imtinen Ben Haj Jilani; Wafa Ben Othman; Wided Megdiche-Ksouri; Zeineb Ghrabi-Gammar; Mohamed Libiad; Abdelmajid Khabbach; Mohamed El Haissoufi; Fatima Lamchouri; et al. (Biology, 2022)
In the context of plant conservation and sustainable use of unique neglected and underutilized phytogenetic resources, this study focused on the Tunisian local endemic Teucrium luteum subsp. gabesianum (Lamiaceae). Using Geographical Information Systems and online databases, detailed taxon-specific ecological profiling was produced for the first time, which illustrated the temperature and climate conditions in its wild habitats and facilitated the investigation of how temperature affects its seed germination, thus making its cultivation in anthropogenic environments possible. Following the seed propagation first reported herein (77.5–81.25% at temperatures between 15 and 25 °C), species-specific in situ and ex situ conservation efforts or sustainable exploitation strategies can be enabled. This study also reported for the first time how chemical and integrated nutrient management (INM) fertilizers affect the growth and pilot cultivation of its seedlings (INM more advantageous). The firstly-reported herein DNA barcoding may enable its traceability, allowing future product design. The multidisciplinary approach followed has paved the way to bridge important research gaps hindering conservation efforts and/or the sustainable exploitation of this local Tunisian endemic plant to date. Based on the aforementioned results, the feasibility and readiness timescale for its sustainable exploitation was overviewed and re-evaluated herein, upgrading (>two-fold) its potential value for the medicinal-cosmetic, agro-alimentary, and ornamental-horticultural sectors.